(untitled) (Revista Peruana de Investigación Educativa, 2024)
This article analyzes the educational choice process of first-generation college students (EPG) who belong to unstable socioeconomic sectors in the Metropolitan area of Lima-Peru. Through an analysis of twenty interviews with a biographical perspective, the article analyzed the role of the family in the choice process, the conceptions about the public and private university offer and the university admission exam as a determining point in the election process. It is argued that educational choices are mediated by the lack of information and orientation about the university, as well as by a segmented educational offer that does not allow them to consider a wide range of options on which to discern. Likewise, the role of families is fundamental, since admission to the university mobilizes resources and aspirations regarding the social and economic transformation of their family group. In this way, the article seeks to discuss the processes of social inequality that occur in the context of the recent massification of university education in Peru and the region.